sNASP Mutation Aggravates to the TLR4-Mediated Inflammation in SLE by TAK1 Pathway - Yatao Bao; Meng Lian; Yong Chen; Xiaotian Gu; Kunyu Cao; Xiaoping Du; Jiyu Ju (Journal of Immunology Research)
Genetic factors play an important role in the pathogenesis of systemic lupus erythematosus (SLE), and abnormal Toll-like receptor (TLR) signaling pathways are closely related to the onset of SLE. In previous studies, we found that the mutant somatic nuclear autoantigenic sperm protein (sNASP) gene in the mouse lupus susceptibility locus Sle2 can promote the development of lupus model mice, but the mechanism is still unclear. Here, we stimulated mouse peritoneal macrophages with different concentrations of lipopolysaccharide. The results showed that sNASP gene mutations can promote the response of the TLR4–TAK1 signaling pathway but have no significant effect on the TLR4–TBK1 signaling pathway. sNASP mutations enhanced TLR4-mediated nuclear factor-κ-gene binding and mitogen-activated protein kinase activation and IL-6, tumor necrosis factor secretion in murine peritoneal macrophages. Collectively, our study revealed the impact of sNASP gene mutation on the sensitivity of TLR4 receptors in mouse peritoneal macrophages and shed light on potential mechanisms underlying inflammation in autoimmune diseases.